2002
DOI: 10.1107/s1600536802011625
|View full text |Cite
|
Sign up to set email alerts
|

L-Histidinium dinitrate

Abstract: Key indicatorsSingle-crystal X-ray study T = 293 K Mean '(C±C) = 0.004 A Ê R factor = 0.036 wR factor = 0.090 Data-to-parameter ratio = 7.4For details of how these key indicators were automatically derived from the article, see http://journals.iucr.org/e. # 2002 International Union of Crystallography Printed in Great Britain ± all rights reserved The title salt, l-HisH 2 2+ Á2NO 3 À , contains two nitrate anions and one l-histidinium dication. The anions and cations are linked to each other through strong hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 11 publications
2
16
1
Order By: Relevance
“…It is reported that LHDN crystallizes in the orthorhombic system with space group P2 1 2 1 2 1 whose unit cell parameters [17]. The synthesis of LHDN has been reported with tiny crystals of size less than 0.5 mm only [12,17]. However, in the present work, we are reporting on the growth of LHDN crystals of relatively big size for the first time.…”
Section: Introductioncontrasting
confidence: 59%
See 2 more Smart Citations
“…It is reported that LHDN crystallizes in the orthorhombic system with space group P2 1 2 1 2 1 whose unit cell parameters [17]. The synthesis of LHDN has been reported with tiny crystals of size less than 0.5 mm only [12,17]. However, in the present work, we are reporting on the growth of LHDN crystals of relatively big size for the first time.…”
Section: Introductioncontrasting
confidence: 59%
“…The crystal structure of LHDN was first reported by Benali-Cherif et al [17] and its spectroscopic properties were explained by Petrosyan et al [7,12]. It is reported that LHDN crystallizes in the orthorhombic system with space group P2 1 2 1 2 1 whose unit cell parameters [17].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The L-His Á 2HNO 3 crystal was also obtained in Ref. [23] and its crystal structure was determined (space group P2 1 2 1 2 1 ). However, as we have recently found out, this crystal was first studied much earlier [24].…”
Section: L-his + Hno 3 + H 2 Omentioning
confidence: 99%
“…This non-common richness in hydrogen bonds is a phenomenon rarely observed in simple organic or mineral compounds; it could be used as a structural model and mime for some reaction mechanisms of the chemical processes in biological media. 4,5 Some hybrid compounds including triphosphates anions and organic cations are known. In these compounds, the acidic triphosphate anions, such us [HP3O10 …”
mentioning
confidence: 99%